The Effect of Debt-to-Equity Ratio and Return on Assets on Stock Returns of Mining Companies on the IDX - Marolip Subyekti; Khaira Amalia; Amlys Syahputra (CV Raskha Media Group, 2025)
This study aims to analyze the effect of Debt to Equity Ratio (DER) and Return on Assets (ROA) on stock returns of mining companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach and involves 15 mining companies during the period 2020–2024. Panel regression analysis is used to determine the effect of leverage and profitability on stock performance. The results show that DER has a negative and significant effect on stock returns, indicating that higher leverage increases risk and reduces investor confidence. Conversely, ROA shows a positive and significant effect on stock returns, indicating that profitable companies tend to generate higher returns for investors. These findings demonstrate the importance of financial performance in shaping investor decisions in the mining sector.